HEALTH AND DISEASE GRAPHICAL EXPRESSION OF IDEAS IN NURSING STUDENTS - Eslava Albarracín, Daniel Gonzalo; Puntel de Almeida, María Cecilia (Investigación y Educación en Enfermería, 2008)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The study tries to give to a passage in the knowledge and the understanding of the knowledge of sense common, that they have the students in relation to the health and the disease, to extend the vision and the knowledge in relation to its forms to think somehow, since, they are going to influence its future behaviors, as much within the institutions of health, like in its daily life. The primary target is the one to identify and to analyze the social representations of health and disease in a group of nursing predegree students, to re.ect surroundings of the daily educational practice and the influence that this one has in the process of construction of knowledge of the students. For the information harvesting the graphical expression of ideas and the focal group were used. The results show that, to acquire or to improve their knowledge, they leave from their own observations of the daily life, re-elaborate their concepts doing them more accessible to their understanding. In relation to the health/disease we cannot speak of certain or missed concepts, simply of forms to include/understand and to live the experience to be healthy or ill, within determined a social and ideological context.